Endophytic Fungi Isolated from Oil-Seed Crop Jatropha curcas Produces Oil and Exhibit Antifungal Activity - Kumar, Susheel (Public Library of Science, 2013)
Jatropha curcas L., a perennial plant grown in tropics and subtropics is popularly known for its potential as biofuel. The plant is reported to survive under varying environmental conditions having tolerance to stress and an ability to manage pest and diseases. The plant was explored for its endophytic fungi for use in crop protection. Endophytic fungi were isolated from leaf of Jatropha curcas, collected from New Delhi, India. Four isolates were identified as Colletotrichum truncatum, and other isolates were identified as Nigrospora oryzae, Fusarium proliferatum, Guignardia cammillae, Alternaria destruens, and Chaetomium sp. Dual plate culture bioassays and bioactivity assays of solvent extracts of fungal mycelia showed that isolates of Colletotrichum truncatum were effective against plant pathogenic fungi Fusarium oxysporum and Sclerotinia sclerotiorum. Isolate EF13 had highest activity against S. sclerotiorum. Extracts of active endophytic fungi were prepared and tested against S. sclerotiorum. Ethyl acetate and methanol extract of C. truncatum EF10 showed 71.7% and 70% growth inhibition, respectively. Hexane extracts of C. truncatum isolates EF9, EF10, and EF13 yielded oil and the oil from EF10 was similar to oil of the host plant, i.e., J. curcas.